Single or Double Induction With 7 1 3 Containing Standard or High-Dose Daunorubicin for Newly Diagnosed AML: The Randomized DaunoDouble Trial by the Study Alliance Leukemia - Röllig, Christoph; Steffen, Björn; Schliemann, Christoph; Mikesch, Jan Henrik; Alakel, Nael; Herbst, Regina; Hänel, Mathias; Noppeney, Richard; Hanoun, Maher; Kaufmann, Martin; Weinbergerova, Barbora; Schäfer-Eckart, Kerstin; et al. (Journal of Clinical Oncology, 2024)
PURPOSE To determine the optimal daunorubicin dose and number of 7 1 3 induction cycles in newly diagnosed AML, this randomized controlled trial compared a once daily dose of 60 mg/m2 with 90 mg/m2 daunorubicin in the first 7 1 3 induction and one versus two cycles of 7 1 3 induction. PATIENTS AND Patients age 18-65 years with newly diagnosed AML were randomly assigned to METHODS 60 versus 90 mg/m2 daunorubicin once daily plus cytarabine. Patients with marrow blasts below 5% on day 15 after first induction were randomly assigned to receive a second induction cycle or no second induction cycle. RESULTS Eight hundred and sixty-four patients with a median age of 52 years were randomly assigned. After a preplanned interim analysis showing no significant difference in response between 60 and 90 mg/m2, all consecutive patients received 60 mg/m2 daunorubicin once daily. The proportion of good early responders was 44% versus 48% (P 5 .983) with a composite complete remission (CRc) rate of 90% versus 89% after induction (P 5 .691); the 3-year relapse-free survival (RFS) after 60 versus 90 mg/m2 once daily was 54% versus 50% (P 5 .561), and the 3-year overall survival (OS) was 65% versus 58% (P 5 .242). Among 389 good responders, CRc rates at the end of induction were 87% after single induction and 85% after double induction. The 3-year RFS was 51% versus 60% (hazard ratio [HR], 1.3; P 5 .091), and the 3-year OS was 76% versus 75% after single versus double induction (HR, 1.0; P 5 .937). CONCLUSION The use of 90 mg/m2 daunorubicin once daily in the context of classical 7 1 3 induction does not significantly improve early response and does not lead to higher remission rates or longer survival than 60 mg/m2 once daily. In patients with a good early response after first induction, a second induction has only a limited impact on RFS and does not result in an OS benefit.
CRIS-Team Scopus Importer:2024-10-04